2011
DOI: 10.1073/pnas.1014218108
|View full text |Cite
|
Sign up to set email alerts
|

Transcript origin analysis identifies antigen-presenting cells as primary targets of socially regulated gene expression in leukocytes

Abstract: To clarify the biological rationale for social regulation of gene expression, this study sought to identify the specific immune cell types that are transcriptionally sensitive to subjective social isolation (loneliness). Using reference distributions for the expression of each human gene in each major leukocyte subtype, we mapped the cellular origin of transcripts found to be differentially expressed in the circulating immune cells from chronically lonely individuals. Loneliness-associated genes derived primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
332
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 261 publications
(361 citation statements)
references
References 49 publications
22
332
1
1
Order By: Relevance
“…In conjunction with the analyses of transcription factor activity, these results suggest that the divergent gene expression profiles observed in hedonic and eudaimonic well-being are mediated by activation of distinct receptor systems within a fixed set of environmentally responsive cell types (33). These findings mirror results from previous studies of adverse experience in identifying a similar set of target cells (34,36,41,42), with eudaimonic well-being in particular showing a reversal of CTRA-related transcription factor dynamics (12,33). These results identify specific psychological, cellular, and molecular targets for future analyses of the social signal transduction pathways that mediate the prospective health advantages of psychological well-being (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In conjunction with the analyses of transcription factor activity, these results suggest that the divergent gene expression profiles observed in hedonic and eudaimonic well-being are mediated by activation of distinct receptor systems within a fixed set of environmentally responsive cell types (33). These findings mirror results from previous studies of adverse experience in identifying a similar set of target cells (34,36,41,42), with eudaimonic well-being in particular showing a reversal of CTRA-related transcription factor dynamics (12,33). These results identify specific psychological, cellular, and molecular targets for future analyses of the social signal transduction pathways that mediate the prospective health advantages of psychological well-being (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 78%
“…Transcription control pathways and cellular origin. Genes showing ≥1.5-fold differential expression across low levels (−2 SD relative to sample mean) vs. high levels (+2 SD relative to sample mean) of eudaimonic well-being and hedonic well-being were tested for (A) differential activity of specific transcription factors as indicated by TELiS analysis of transcription factor-binding motifs (TFBM) in proximal promoter sequences of up-vs. down-regulated genes (40) and (B) PBMC cell type of origin as indicated by TOA cell-type diagnosticity z-scores (36). (*P < 0.05 after control for multiple hypothesis testing.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Diminished physical activity 13 • Diminished motor function 14,15 • Symptoms of depression 16 • Disrupted sleep and daytime dysfunction 17 • Impaired mental and cognitive function 18 • Increased systolic blood pressure 19 • Increased sympathetic tone and vascular resistance 20,21 • Increased hypothalamic pituitary adrenocortical activity 22,23 • Altered gene expression related to anti-inflammatory responses 24 • Altered immunity 25,26 Of greater concern, however, is an accumulating volume of research that highlights loneliness as a risk factor for both functional decline as well as increased mortality. 4,8,[27][28][29] In short, there is evidence that the subjective experience of loneliness can significantly contribute to premature death independently of other physical, behavioral, or psychological factors.…”
Section: Effects Of Lonelinessmentioning
confidence: 99%
“…Studies designed to identify the mechanisms underlying the association between loneliness and mortality have found that loneliness is associated with increased hypothalamic-pituitary-adrenocortical (HPA) activity (Adam et al, 2006;Cacioppo et al, 2006;Doane and Adam, 2010;Glaser et al, 1985;Kiecolt-Glaser et al, 1984;Steptoe et al, 2004), altered gene expression indicative of decreased inflammatory control and increased glucocorticoid insensitivity (Cole et al, 2007(Cole et al, , 2011, increased inflammation, elevated vascular resistance, and blood pressure (Hackett et al, 2012;Hawkley et al, 2006Hawkley et al, , 2010bJaremka et al, 2013), higher rates of metabolic syndrome (Whisman, 2010), diminished immunity (Dixon et al, 2006;Glaser et al, 2005;Kiecolt-Glaser et al, 1984;Pressman et al, 2005;StraitsTröster et al, 1994), increased risk for age-related cognitive decline and dementia (Wilson et al, 2007), and increased sleep fragmentation (Cacioppo et al, 2002;Hawkley et al, 2010a;Jacobs et al, 2006;Kurina et al, 2011). Cross-lagged panel analyses have also shown that loneliness has also been associated with changes in psychological states that can contribute to morbidity and mortality, including increased depressive symptomatology (Booth, 2000;Cacioppo et al, 2006Cacioppo et al, , 2010VanderWeele et al, 2011), lower subjective wellbeing (Kong and You, 2013;VanderWeele et al, 2012), heightened vigilance for social threats (Cacioppo et al, 2015b), and decreased executive functioning (Baumeister and DeWall, 2005;Cacioppo et al, 2000;…”
Section: Introductionmentioning
confidence: 99%